Sedimentation of the Jianggalesayi basin and its response to the unroofing history of the Altyn Tagh, northern Tibetan Plateau - Chen, Zhengle; Wang, Xiaofeng; Liu, Jian; Chen, Xuanhua; Sun, Zhiming; Pei, Junling (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 114-115